2023
DOI: 10.2807/1560-7917.es.2023.28.19.2200568
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial resistance of clinical Enterobacterales isolates from urine samples, Germany, 2016 to 2021

Carolin Stoltidis-Claus,
Kerstin Daniela Rosenberger,
Falitsa Mandraka
et al.

Abstract: Introduction Empirical therapy for the treatment of urinary tract infections should be tailored to the current distribution and susceptibility of potential pathogens to ensure optimal treatment. Aim We aimed to provide an up-to-date overview of the epidemiology and susceptibility of Enterobacterales isolated from urine in Germany. Methods We retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Notably, among our small panel, we identified two clinical isolates that exhibited susceptibility exclusively to NTX, while being resistant to all other tested drugs. Recently, Stolditis-Claus et al demonstrated that NTX has the lowest resistance rate (3.9%, 48 out of 1,246 NTX data sets) among all commonly used antibiotics against Enterobacteriales (FOS 4.6%, NFT 11.7%, CIP 14.2%, TMP 24.2%, and PIV 30%) isolated from urine samples in Germany (total number of isolates n = 201,152) and concluded that its effectiveness has not decreased in recent years ( 9 ). Hof et al ( 20 ) evaluated 477 isolates from urine samples and described excellent activity of NTX against E. coli with only 1 out of 277 isolates being resistant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, among our small panel, we identified two clinical isolates that exhibited susceptibility exclusively to NTX, while being resistant to all other tested drugs. Recently, Stolditis-Claus et al demonstrated that NTX has the lowest resistance rate (3.9%, 48 out of 1,246 NTX data sets) among all commonly used antibiotics against Enterobacteriales (FOS 4.6%, NFT 11.7%, CIP 14.2%, TMP 24.2%, and PIV 30%) isolated from urine samples in Germany (total number of isolates n = 201,152) and concluded that its effectiveness has not decreased in recent years ( 9 ). Hof et al ( 20 ) evaluated 477 isolates from urine samples and described excellent activity of NTX against E. coli with only 1 out of 277 isolates being resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it seems that only low-level resistance against NTX can be achieved with MIC values still below the maximal concentration of NTX determined in urine samples ( 28 ), making the reduced susceptibility of in vitro generated mutants less of a concern. Other common drugs used for the treatment of UTI were characterized by mutants developing at a higher frequency with high levels of resistance (over 2,000-fold shifts in MIC) which can explain increased resistance rates in clinical samples ( 9 ). Thus, in this head-to-head comparison, we found NTX clearly superior in terms of its resistance development properties in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 summarizes the resistance rate to nitrofurantoin among strains of E. coli causing UTI. The results come from studies performed in different regions of the world, in different periods, and in groups of different sizes [ 2 , 7 , 8 , 10 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In most cases, the percentage of resistance to nitrofurantoin was low and often did not exceed 3%.…”
Section: Introductionmentioning
confidence: 99%